JOUVE MARTIN, José R., 2014, The Black Doctors of Colonial Lima: Science, Race,and Writing in Colonial and Early Republican Peru, Montreal, Kingston, Londres eIthaca, McGill-Queen’s University Press. 210 pp. - Lerner, Adrián (2015)
Se reseñó el libro: The Black Doctors of Colonial Lima: Science, Race, and Writing in Colonial and Early Republican Peru.